A model of structural analysis for multi-storey buildings with ETABS software - Dương Hồng Thẩm (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kỹ thuật và Công nghệ)
During the process of instructing the course Design of Multi-storey Buildings in the curriculum for Undergraduate developed by the Faculty of Civil Engineering in the Ho Chi Minh City Open University, modeling the structural system using professional packages such as SAP2000, ETABS, etc., is notably taught in the practice (within 30 period hours). For the learning outcome of the course, that is, to properly model the structural system of the building, one of the main requirements is to help learners easily practice, create, and solve the model, i.e., by some specific input data such as prescribing the element properties, assigning the loads and solving properly the model, to analyze the output in an acceptable level of accuracy. The fact is that, during the course, students have not sufficiently modeled the system, therefore the results (values of element dimensions, cross-section, etc.) are unreliable. This paper aims to point out a rigorous procedure of input data and to introduce the main content of structural modeling, with some necessary techniques, which in turn, the results of the analysis could be applied to reality. A few of the time-dependent properties of the material, concerning the column shortening, and geometric nonlinear P-Δ effects are considered in a dynamic analysis and other kinds of analyses. This study for tutorial purposes is necessary for the teaching staff, undergraduate engineering students, and partially beneficial for designers using ETABS in analysing the multi-storey buildings. Without any course outcome assessment, the limitation of the study is tentatively outlined.